Legal Verses About Women's Dignity and Actualization of Gender Equality in the Family - Nawawi, M Anwar; Zainuri, Muhammad; AB, Balik Jaya; Ibrahim, Rosita (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
This article is about legal verses related to the noble status of women. So far, some people still think that the status of women is not as special as that of men. Such an assumption has a serious impact on gender inequality in the household, women are often positioned as officers who play a role in "wells, kitchens and mattresses". Whereas in the Qur'an the position of men and women in the family sphere has the same degree, has the same rights and obligations, has the same dignity. The focus of this article is to find the verses of women's law and their actualization of gender justice in the family. This type of article is library research (literary research), using a qualitative approach with discriminatory-analytic analysis, this article explains the verses about the glory of women in Islam. From several stories in the Koran, especially verses about the glory of women. It can be said that Islam came to proclaim the humanity of women as whole human beings. Women are noble beings who have dignity and worth. Islam asserts that all humans (male and female) are created from the same element (nafs wahidah). Islam is very strict about placing women as equal partners to men, including in the family.